Cardiac septic pulmonary embolism: A retrospective analysis of 20 cases in a Chinese population. Issue 25 (June 2016) - Song, Xin yu; Li, Shan; Cao, Jian; Xu, Kai; Huang, Hui; Xu, Zuo jun
Abstract : Abstract: Based on the source of the embolus, septic pulmonary embolism (SPE) can be classified as cardiac, peripheral endogenous, or exogenous. Cardiac SPEs are the most common. We conducted a retrospective analysis of 20 patients with cardiac SPE hospitalized between 1991 and 2013 at a Chinese tertiary referral hospital. The study included 14 males and 6 females with a median age of 38.1 years. Fever (100%), cough (95%), hemoptysis (80%), pleuritic chest pain (80%), heart murmur (80%), and moist rales (75%) were common clinical manifestations. Most patients had a predisposing condition: congenital heart disease (8 patients) and an immunocompromised state (5 patients) were the most common. Staphylococcal (8 patients) and Streptococcal species (4 patients) were the most common causative pathogens. Parenchymal opacities, nodules, cavitations, and pleural effusions were the most common manifestations observed via computed tomography (CT). All patients exhibited significant abnormalities by echocardiography, including 15 patients with right-sided vegetations and 4 with double-sided vegetations. All patients received parenteral antimicrobial therapy as an initial treatment. Fourteen patients received cardiac surgery, and all survived. Among the 6 patients who did not undergo surgery, only 1 survived. Most patients in our cardiac SPE cohort had predisposing conditions. Although most exhibited typical clinical manifestations and radiography, they were nonspecific. For suspected cases of SPE, blood culture, echocardiography, and CT pulmonary angiography (CTPA) are important measures to confirm an early diagnosis. Vigorous early therapy, including appropriate antibiotic treatment and timely cardiac surgery to eradicate the infective source, is critical.